2020
DOI: 10.1371/journal.pone.0233412
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia using dezocine alleviates depressive symptoms after colorectal cancer surgery: A randomized, controlled, double-blind trial

Abstract: BackgroundPostoperative depression is one of the most common mental disorders in patients undergoing cancer surgery and it often delays postoperative recovery. We investigated whether dezocine, an analgesic with inhibitory effect on the serotonin and norepinephrine reuptake, could relieve postoperative depressive symptoms in patients undergoing colorectal cancer surgery. MethodsThis randomized, controlled, single-center, double-blind trial was performed in the Second Affiliated Hospital of the Army Medical Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Dezocine has been found to inhibit both the serotonin and norepinephrine uptake transporters [1]. This led to the investigation and discovery that dezocine has antidepressant activity in patients treated post-operatively for pain [22]. Anti-depressant activity of dezocine was also verified in a rodent model [23].…”
Section: Discussionmentioning
confidence: 99%
“…Dezocine has been found to inhibit both the serotonin and norepinephrine uptake transporters [1]. This led to the investigation and discovery that dezocine has antidepressant activity in patients treated post-operatively for pain [22]. Anti-depressant activity of dezocine was also verified in a rodent model [23].…”
Section: Discussionmentioning
confidence: 99%
“…Dezocine is a potent opioid analgesic with both exciting and antagonistic effects ( 12 ). On the one hand, dezocine mainly achieves analgesic and sedative effects by exciting K receptors distributed in the brain, spinal cord, and brain stem ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…74 Zhao et al also confirmed this finding in patients after colon cancer surgery. 75 These results suggest that dezocine has an antidepressant effect both in cancer patients undergoing surgery and in pregnant women undergoing cesarean section. An experimental study has found that dezocine exerts antidepressant-like effects in mice through the involvement of 5-HT1A and κ opioid receptors.…”
Section: Dezocine Has Potential To Regulate the Clinical And Biologic...mentioning
confidence: 94%